2014
DOI: 10.1007/s12046-013-0225-2
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent jet in confined counterflow

Abstract: Abstract. The mean flowfield of a turbulent jet issuing into a confined, uniform counterflow was investigated computationally. Based on dimensional analysis, the jet penetration length was shown to scale with jet-to-counterflow momentum flux ratio. This scaling and the computational results reproduce the well-known correct limit of linear growth of the jet penetration length for the unconfined case when the momentum flux ratio is small. However, for the high momentum flux ratio case corresponding to the confin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
2
5
0
Order By: Relevance
“…Since x axis is co-directional with mass-averaged crossflow velocity U m as depicted in The latter demonstrates only linear dependence J 1/2 according to formula (2). The former turned out to consist of linear region  J 1/2 (or h/D) within 4<J 1/2 <30 (formula ( 2)), the non-linear region  J 1/6 (or (h/D) 1/3 ) within 30<J The obtained complicated dependence h v /D = f(J 1/2 ) looks very similar to that discovered in [8,9] when counter-flowing jet issues from centerline-located tube toward a mainstream flow of cylindrical duct (equi-density flows).…”
Section: Resultssupporting
confidence: 74%
“…Since x axis is co-directional with mass-averaged crossflow velocity U m as depicted in The latter demonstrates only linear dependence J 1/2 according to formula (2). The former turned out to consist of linear region  J 1/2 (or h/D) within 4<J 1/2 <30 (formula ( 2)), the non-linear region  J 1/6 (or (h/D) 1/3 ) within 30<J The obtained complicated dependence h v /D = f(J 1/2 ) looks very similar to that discovered in [8,9] when counter-flowing jet issues from centerline-located tube toward a mainstream flow of cylindrical duct (equi-density flows).…”
Section: Resultssupporting
confidence: 74%
“…Several works about jets in counterflow and crossflow have converged into a similar empirical mathematical expression for describing h (eq ). , K is a dimensionless empirical constant that depends on the mixing length and shear layer of the gases, Z is the ratio that relates the initial momentum of the jet with the momentum of the opposing or retarding flow, and D is the inner diameter of the confinement tubing. We suggest that Z is best represented by the ratio of the jet-to-backward momentum flows , ( J n / J p ) (eq ).…”
Section: Resultsmentioning
confidence: 99%
“…Several works about jets in counterflow and crossflow have converged into a similar empirical mathematical expression for describing h (eq 2). 32,33…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Compared to co-and cross-flows above, studies on inclined dense jets in counter-flows are even fewer, and the reported mixing behavior is more complex with marked instabilities due to the reverse flow (Sivapragasam et al 2014). Figure 5.1(b) shows a schematic diagram of the inclined dense jet issuing into a strong counter-flow.…”
Section: Smagorinsky Sgs Modelmentioning
confidence: 99%
“…Compared to co-and cross-flows above, studies on inclined dense jets in counter-flows are even fewer, and the reported mixing behavior is more complex with marked instabilities due to the reverse flow (Sivapragasam et al 2014). Previous studies for non-buoyant jets in counter-flows gave substantial attention on the penetration depth (the definition of penetration depth x p is referred in Chapter 5).…”
Section: Dimensional Analysismentioning
confidence: 99%